GAMBARAN DIRI IDEAL REMAJA AKHIR JAWA MASA KINI - , LULUUL UMAMI; , Prof. Johana E. Prawitasari, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The aim of this research is to the ideal self description and how far the validity of characteristic from ideal self of late adoles Javanese today like competence and independent and the other of characteristic which found in Nuryoto, Rahardanto, Umami, and Rayani in 2010. The subject of this research is 145 colleges, consist of 61 males and 84 female students, among 18 to 24 years old. Two kinds of scales are used to collect data, giving frequently. Section one (Scale of view thyself), and Section two (Scale of view thyself to others). Exploratory factor analysis is used to precede the data. The results show that the competence and independent not ever be disposed to Javanese late adolescents because both characteristics not be constituent part of the ideal self description of late adoles Javanese. Besides, known that valid characteristics such outgoing, intellect, adaptive, kind, and assertive. The results of the analysis show that formed new characteristics, such loyal, responsible, and persistent.